2011
DOI: 10.1002/clen.201000588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co‐culture and Nutrients Supplementation on Bioremediation of Crude Petroleum Sludge

Abstract: Ex-situ bioremediation of real-field crude petroleum sludge was evaluated to elucidate the role of co-culture (bioaugmentation) and external nutrients supplementation (biostimulation) under anaerobic microenvironment. Maximum removal of total petroleum hydrocarbons (TPH) was observed by integrating biostimulation with bioaugmentation (R5, 44.01%) followed by bioaugmentation alone (R4, 34.47%), co-substrate supplemented operations [R6, 23.36%; R3, 16.5%; R2, 9.88%] and control (R1, 4.36%). Aromatics fraction sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
0
12
0
4
Order By: Relevance
“…Chong et al also reported that most of the Antarctic soil environments contained a narrow range of bacterial species . Hence, to make bioremediation successful, introduction of microorganisms which have the capacity to degrade toxic compounds is a more effective methodology .…”
Section: Resultsmentioning
confidence: 99%
“…Chong et al also reported that most of the Antarctic soil environments contained a narrow range of bacterial species . Hence, to make bioremediation successful, introduction of microorganisms which have the capacity to degrade toxic compounds is a more effective methodology .…”
Section: Resultsmentioning
confidence: 99%
“…Various carbon and nitrogen sources such as dextrose, maltose, yeast extract and peptone (0.1%) were added to the MSM medium containing 4% diesel oil as nutrient addition for diesel oil degradation, amongst them peptone and yeast extract were found to enhance diesel oil degradation). Prathima Devi et al [19] reported that addition of external nutrients enhance the degradation of crude petroleum sludge. As shown in Figure 6, growth of A. baumannii was increased in the presence of peptone within 120 h. Consequently, peptone was selected as the nitrogen source for further studies.…”
Section: Resultsmentioning
confidence: 99%
“…and Bacillus cereus, respectively. Devi et al (2011) reported biodegradation of a crude oil using anaerobic Fig. 1.…”
Section: Poly-aromatic Compounds Degradationmentioning
confidence: 98%